Boreal Headwater Catchment as Hot Spot of Carbon Processing From Headwater to Fjord. Issue 12 (2nd December 2021) - Clayer, F.; Thrane, J.‐E.; Brandt, U.; Dörsch, P.; de Wit, H. A.
Abstract: Boreal headwaters and aquatic sediments are significant transporters, stores and processors of terrestrial carbon (C) as well as emitters of greenhouse gases (GHGs), mainly CO2 and CH4 . While terrestrial ecosystems are net sinks of atmospheric C, lateral fluxes of total organic and dissolved inorganic C (TOC, DIC) as well as GHG release can significantly reduce the land C sink. However, the fate of the laterally exported C remains often unresolved. Here, we combine datasets from high‐frequency sensors, monitoring and modeling to produce a C budget for a typical boreal lake and its catchment and examine it in a regional context. We show that lake TOC removal is dominated by microbial metabolism which shows strong seasonal fluctuations following stratification and ice‐cover dynamics. We estimate that 11.5 g C m −2 catchment yr −1 are exported from the catchment soils and wetlands, including 9.5 g of TOC. Only 5.4 g C m −2 catchment yr −1 reach the coast while over 50% is reemitted to the atmosphere (5.7 g C m −2 catchment yr −1 ). Part of the reemitted C originates from rapid turnover cycles and would not affect atmospheric CO2 and the land C sink. However, we show that the land C sink at Langtjern is reduced by >14% over the whole aquatic continuum, and by >10% within the headwater catchment. Our regional analysis suggests that headwater lake TOC mineralization is the main TOC loss along the aquatic continuum with burial being relatively small, and highlights the significance of small headwaters as intensive and fast‐responding TOC processors. Plain Language Summary: Small boreal lakes and streams are intensive sites of carbon (C) processing and greenhouse gas (GHG) emissions. While trees and other plants in the boreal forest capture atmospheric C, soil C losses through aquatic export of organic C and GHG evasion can reduce this land C capture with consequences on global warming and the climate system. The magnitude of these aquatic fluxes remain largely unresolved. In this study, we quantified the C fluxes from Norwegian mountainous (moderate elevation) lakes and streams to fjord and show that mountainous aquatic environments are fast‐responding and intensive sites of C processing. More than 35% of the organic C exported from soils is transformed to GHG before reaching the fjord, of which 67% happens within 4 km of C fixation in the forest. In total, we estimate that about 20% of the C fixed in the forest, likely more, is counterbalanced by GHG emissions from aquatic environments, especially within small lakes and streams. Key Points: A carbon budget shows that microbial metabolism is the dominant organic carbon transformation pathway in a typical Norwegian boreal lake At least 35% of the organic carbon exported from a typical South Norwegian catchment is mineralized before reaching the fjord Over 67% of the organic carbon mineralization occurs in the headwater catchment highlighting the role of headwaters in carbon cycling